The Mirror House girls : a psychological thriller - Gardner, Faith (Mirror House Press, 2025)
"An isolated compound. A so-called family. A collision course with unthinkable violence. When Winona rents a room at the eccentric Mirror House, she hopes to make new friends. What she gets instead is a "family" led by the charismatic psychologist Simon Spellmeyer. But if she wants to stay at Mirror House, Winona must join in following Simon's strange protocols for self-improvement. Warning bells chime inside her, yet the allure of transformation keeps her there. His methods are disturbing, but the results are undeniable. Soon, Simon's vision for their future spirals in a darker direction. The group relocates, expands, and Winona's once-close bond with her housemates grows fractured by mistrust until she's trapped among people she hardly recognizes. Including herself. Can Winona wake up to the true cost of Simon's vision in time to get out alive? Or will the utopian dream descend into a tragic nightmare?"--